Iron binding to caseins in the presence of orthophosphate. (1st January 2016) - Mittal, V.A.; Ellis, A.; Ye, A.; Edwards, P.J.B.; Das, S.; Singh, H.
Highlights: Investigation into the addition of iron to sodium caseinate solutions. Addition of orthophosphate to the mixture prevented iron/casein precipitation. Insights into the formation of a iron–casein–orthophosphate complex. Abstract: As adding >5 mM ferric chloride to sodium caseinate solutions results in protein precipitation, the effects of orthophosphate (0–64 mM) addition to sodium caseinate solution (2% w/v protein) on iron-induced aggregation of the caseins were studied at pH 6.8. Up to 20 mM ferric chloride could be added to sodium caseinate solution containing 32 mM orthophosphate without any protein precipitation. The addition of iron to sodium caseinate solution containing orthophosphate reduced the diffusible phosphorus content in a concentration-dependent manner. Added iron appeared to interact simultaneously with phosphoserine on the caseins and inorganic phosphorus. The relative sizes of the casein aggregates were governed by the concentration of orthophosphate and the aggregates consisted of all casein fractions, even at the lowest level of ferric chloride addition (5 mM). It is hypothesised that the addition of iron to caseins in the presence of orthophosphate results in the formation of colloidal structures involving casein–iron–orthophosphate interactions.